Effects of steaming pre-treatment and compression level on properties of oil palm wood - Abare, Alhassan Yakubu (2014)
There are various technical problems in the current processing technology to convert oil palm trunks to lumber and other useful products. Sawing of oil palm wood andtime in drying and heating are generally considered difficult by industry. The main objective of this study was to evaluate the effect of steaming pre-treatment and compression level during hot press on the properties of oil palm wood produced using integrated processing and approach method.The research was divided into two phase viz; Comparison of sawing patterns and treatment Processes of oil palm wood (OPW). In the comparison of sawing patterns, two of sawing patterns were adopted from cant sawing and named as modified cant sawing (MCS) and reverse cant sawing (RCS).The process of each sawing pattern was divided into 5 work elements: (a) sawing pattern mapping (b) transporting log from log-yard to log-deck (c) loading log to carriage (d) sawing (Head rig) and (e) re-sawing. The total sawing time for each sawing pattern was calculated. The total sawing time comprises both the effective and ineffective time. This was used in the comparison of the two sawing methods. For the treatment processes,three palm trees (≥ 28-year) were harvested and debarked using the Spindle-less peeler and thereafter sawn with a reverse cant sawing pattern (RCS) to get slabs which were edged to form samples with measurements of 30cm long, 6 cm thickness and 15cm width. The samples were then steamed and cold compressed at various compression percent (0%, 20%, 30%, and 40%),drying was carried outat a targeted moisture content of 15 percent. Then it was treated with low molecular weight phenol formaldehyde (LMW-PF) in an impregnation cylinder. Subsequently, the samples were further dried to moisture target of 70 percent in an oven, and finally hot densification to 50% of the original thickness for 45 minutes. The results obtained from comparison of the two sawing patterns were further compared with secondary data of polygon sawing (PS). The total sawing time of reverse cant sawing, modified cant sawing, and polygon sawing was 842 seconds, 919 seconds and 2760 respectively. The total sawing time of PS was more than three times (2760 second) any of these two types of sawing pattern. The result from the treated test samples showed that the physical properties showed that, steamed samples with 40% compression level has the highest density (1065.23 kg/m3) while the lowest density was recorded at un-steamedsamples with 0% compression level (766.13 kg/m3). The density showed an increasing trend from 0% to 40% level for both the steamed and un-steamed samples. Similarly, the density gain and weight percent gain showed almost the same trend. The analysis of variance showed that steaming was not significant on most of the physical properties while the compression level was significant in most of the physical properties.The mean values of the Modulus of Elasticity (MOE) and Modulus of rapture (MOR)ranges from 5687.34 MPa -15046.53 MPa and 42.57 MPa to 114.57MPa respectively. Steaming does not have significant effect on both MOE and MOR while compression level showed significant for both MOE and MOR.From the result, it was found that RCS is the most suitable sawing pattern to produce OPW, because it consumed the shortest total sawing time and it is easy to carry out.In the treatment processes, steaming of the wood samples for this research did not give much effect on variables measured for this study, this implies that it is not necessary for this study. The compression level (%) has great role in this research because it helps in improving the properties of the treated compreg OPW. The compression levels that can be consider most suitable is either 30% or 40%. A patent has already been applied for this research work.